Auditing the auditors – any impact? - Lim, Yan Kong; Mustapha, Mazlina (2015)
Audit Oversight Board (AOB) was established in Malaysia in 2010 to regulate the auditors of public interest entities (PIEs), and to instil the trust and confidence of the public on the quality of services provided by the auditors. This study attempts to explore the impact of AOB establishment on the external auditors in Malaysia. Interviews were conducted with twenty audit seniors and managers in Bigfour and non-Big four firms in Selangor and Kuala Lumpur. Among others the interviews reveal that more works are done and more documentation is compiled after AOB establishment. However, the auditors claimed that their reliance on the internal auditors is not affected by AOB establishment. The findings also suggest that audit fee is not directly affected by the establishment of AOB. The results of the study contribute to the literature and understanding of AOB establishment in Malaysian audit industry.